Energy losses of fast light ions and plasmon excitation in metal films - Kononenko, S.I.; Kalantaryan, O.V.; Zhurenko, V.P. (Вопросы атомной науки и техники, 2005)
In this paper, we present the results of measurements of the secondary emission electrons (SEE) coefficients and electron energy distributions in the forward and backward directions. The measurements were carried out in experiments with three different substances. Generalizing the results obtained makes it possible to determine the mechanisms for energy losses of a fast ion propagating in solid-state plasma. The present investigation is dedicated to thick silver foil ionoluminescence study under different incident angles and proton energies also. Possible mechanisms of light generation are discussed based on obtained experimental data. У цій роботі представлені результати вимірів енергетичних розподілів електронів і коефіцієнтів вторинної іонно- електронної емісії на простріл і на відбиття. Експерименти проведені для трьох речовин. Узагальнення отриманих результатів дозволило визначити механізми втрат енергії швидкими іонами, що рухаються у твердотільній плазмі. Ця робота також присвячена вивченню іонолюмінесценції товстої срібної фольги при різних кутах падіння та енергіях протонів. Виходячи з отриманих експериментальних даних обговорюються можливі механізми генерації світла. В этой работе представлены результаты измерений энергетических распределений электронов и коэффициентов вторичной ионно-электронной эмиссии на прострел и на отражение. Эксперименты проведены для трех веществ. Обобщение полученных результатов позволило определить механизмы потерь энергии быстрыми ионами, движущимися в твердотельной плазме. Настоящая работе также посвящена изучению ионолюминесценции толстой серебряной фольги при различных углах падения и энергиях протонов. Исходя из полученных экспериментальных данных обсуждаются возможные механизмы генерации света.